Morphological and phylogenetic evaluation of a new species of Rhodoveronaea (Rhamphoriaceae, Rhamphoriales) associated with Quercus fabrei (Fagales) in Yunnan Province, China - Yan-Yan Yang; Chitrabhanu Bhunjun; Vinodhini Thiyagaraja; Pattana Kakumyan; Darbhe Bhat; Fatima Al-Otibi; Tai-Shun Li; Qi Zhao; Kevin D. Hyde (Biodiversity Data Journal)
During an extensive mycological exploration of Fagales-associated mycoflora within the biodiverse landscapes of Yunnan Province, China, we discovered a new saprotrophic fungal species. Based on its unique morphological characteristics and phylogenetic analyses of combined LSU, ITS, SSU, tef1-α and rpb2 sequences, we established Rhodoveronaea querci as a new member of the genus Rhodoveronaea, which was collected from Quercus fabrei colonising terrestrial habitats.Rhodoveronaea querci is currently only known from its asexual form, which is a morphologically distinct hyphomycete fungus. The distinguishing characteristics of R. querci are straight or slightly flexuous, septate and unbranched conidiophores, terminally, integrated, apically protuberant, recurved conidiogenous cells with conspicuous conidiogenous loci and ellipsoidal to narrowly-obovoid, mostly 1-septate, slightly constricted at the central septum, guttulate, conidia with a flat basal scar. Rhodoveronaea querci and R. hainanensis are highly similar in the size and shape of their conidiophores and conidia, but they can be distinguished by other morphological characteristics and by genetic differences. Rhodoveronaea species are widely distributed in Europe and Asia and recent studies revealed several new Rhodoveronaea species from China.